Paradigm of Historical Axiomatism Beyond New Institutionalism: Rebuilt of Management (I) for New Civilization. Issue 2 (December 2019) - Zongcheng, Li
This article puts forth the hierarchical sequence of ontology beyond the experience of the new institutionalism: arche, paradigm, pattern, structure and factors; thus, the analytic framework of the ontology and its axiomatism of complex organizations analysis framework is set. In the new research, the core of the complex organization is attributed to the structure of rights and interests, the dynamics base of complex organizations is attributed to the dynamic system and the right–interest relation, while the dynamic system is concentrated in two aspects: system function–system load and system efficiency–system consumption; the right–interest relation are concentrated on interest structures, human right structures and sovereignty structures. From the personal level to the national level, from the political field to the rest of the society, this series discuss the relationship between interests, human rights and sovereignty, where the right–interest relation, rule framework, game organization and ecological mode are interrelated and mutually determined.